Malaysian Youth, Social Media Following, and Natural Disasters: What Matters Most to Them? - Ismail, Nurzali; Ahmad, Jamilah; Noor, Shuhaida Md.; Saw, Jayslyn (Registrar of Newspapers for India (RNI), 2019)
This study attempted to understand youth’s social media following during natural disasters. It investigated Malaysian youth’s perception about the importance of immediacy, trust, and accuracy of social media news and information during natural disasters. This study found that youth prefer to consume social media news and information during natural disasters such as flooding, landslides, and haze. This is mainly contributed by the immediacy of news and information on social media. Besides immediacy, youth also value trust and accuracy of social media news and information during natural disasters. As the findings of this study revealed, youth are more inclined to become followers to social media creators who have a high level of trust and whom they believe can provide accurate natural disasters news and information. Hence, it is crucial that the authority and news organizations to provide natural disasters news on social media that is timely and accurate.